2018
DOI: 10.1021/acs.chemmater.7b04628
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation of Few-Layer Black Phosphorus in Low-Boiling-Point Solvents and Its Application in Li-Ion Batteries

Abstract: The liquid-phase exfoliation (LPE) of black phosphorus (BP) is a strategic route for the large-scale production of phosphorene and few-layer BP (FL-BP) flakes. The exploitation of this exfoliated material in cutting-edge technologies, e.g., in flexible electronics and energy storage, is however limited by the fact that the LPE of BP is usually carried out at a high boiling point and in toxic solvents. In fact, the solvent residual is detrimental to device performance in real applications; thus, complete solven… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 94 publications
1
81
0
Order By: Relevance
“…Owing to the outstanding physical and chemical property of BP as a rising star, BP has been applied in many fields such as batteries anodes, selective sensors, and field‐effect transistors, and these applications have been reviewed by many articles . Apart from aforesaid applications, BP, as a promising photocatalyst, has been applied in the field of photocatalysis for solar‐to‐energy conversion, photocatalytic carbon dioxide reduction, photocatalytic hydrogenation, environmental pollutants treatment, solar‐driven nitrogen fixation and antibacterial application, and cancer treatments.…”
Section: Photocatalysis Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the outstanding physical and chemical property of BP as a rising star, BP has been applied in many fields such as batteries anodes, selective sensors, and field‐effect transistors, and these applications have been reviewed by many articles . Apart from aforesaid applications, BP, as a promising photocatalyst, has been applied in the field of photocatalysis for solar‐to‐energy conversion, photocatalytic carbon dioxide reduction, photocatalytic hydrogenation, environmental pollutants treatment, solar‐driven nitrogen fixation and antibacterial application, and cancer treatments.…”
Section: Photocatalysis Applicationsmentioning
confidence: 99%
“…In the past few years, there are many articles that have reported the practical application of BP in batteries, photodetectors, sensors, field‐effect transistors, and solar cells, and these applications have been summarized in some reviews . Meanwhile, many papers have reported the application of photocatalysis field, while there is no article that has detailedly reported that BP as a photocatalyst is employed in various aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Many layered materials such as graphite,M oS 2 ,S n 4 P 3 ,a nd black Pa re being studied for their electrochemical applications in lithium-ionb atteries. [1,2,[12][13][14][15][16][27][28][29][30][31][32][33][34] Theoryh as predicted that tetrel-based layered graphitea nalogs, silicene, germanene, and stanene may be suitable for battery applications. [35,36] In addition, lithiated tetrels with layered structures have been studied to better understandt he reactionp rocesses occurring in Ge and Si anodes.…”
Section: Introductionmentioning
confidence: 99%
“…An indirect way to gain insight into the affinity of the solvent molecules for the BP consists in the ability of the given solvent to disperse the 2D material, e.g., in the case of liquid phase exfoliation. Previous work revealed that BP is poorly dispersed in solvents with lower surface tension such as acetone, IPA and ethanol, which implies an unfavorable adhesion of these solvent molecules onto the surface of BP . In other words, the number of molecules physisorbed in a given surface area of BP for these three solvents is smaller when compared to aromatic solvents.…”
Section: Resultsmentioning
confidence: 98%